Gut Microecology of Four Sympatric Desert Rodents Varies by Diet - Dongyang Chu; Haoting Zhang; Zhenghaoni Shang; Nan Liu; Heping Fu; Shuai Yuan (Ecology and Evolution)
ABSTRACT The gut microbiome can be one pathway by which a host rapidly acclimates and adapts to its ecological environment. Exploring how the microbiome has evolved to differ between hosts with different diets provides insights into the profound interactions between hosts and microbes within these systems. In this study, we used DNA metabarcoding techniques and macrogenomic prediction techniques to study the gut microbes of four desert rodent species with different feeding strategies in the same habitat. One species is herbivorous (Spermophilus alashanicu)s, one is granivorous (Phodopus roborovskii), another is omnivorous (Dipus sagitta), and the last (Orientallactaga sibirica) has a diet with a relatively high proportion of insects. Diets rich in plants and insects can be challenging to digest due to the abundance of indigestible fiber and stable chitin, respectively. Out of the species studied, the herbivorous Spermophilus alashanicus has the highest density of UCG‐005 genes and the highest predicted abundance of genes related to digestive complexity. The composition of Phodopus roborovskii's microbiome has the highest variation between individuals, yet Phodopus roborovskii has the highest predicted abundance of genes associated with simple sugars—reflecting this species' potential adaptability to the starch within plant seeds and its constraints brought about by its smaller body size. The most insectivorous species, Orientallactaga sibirica, exhibits the highest predicted abundance of genes related to chitin degradation. This study has enhanced our understanding of the gut microbiota in the intestines of rodents as they adapt to various dietary strategies.